2011
DOI: 10.1258/ar.2011.100322
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of organ-absorbed radiation doses during 64-detector CT coronary angiography using different acquisition techniques and heart rates: a phantom study

Abstract: ECG-triggered non-helical acquisition is recommended to reduce the radiation dose. Also, controlling the patients' heart rate appropriately during ECG-gated helical acquisition with ECGM is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Our study supports the use of tube voltage and heart rate reduction to decrease ARD and is in synchrony with Matsubara et al who obtained similar results on phantom studies with 64-row CT angiography [18]. Litmanovich et al [20] also found better ARD profile in 64-row MDCT phantom study by using imaging protocols with lower tube voltage which was in consensus with an earlier study by Hurwitz et al [21, 22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study supports the use of tube voltage and heart rate reduction to decrease ARD and is in synchrony with Matsubara et al who obtained similar results on phantom studies with 64-row CT angiography [18]. Litmanovich et al [20] also found better ARD profile in 64-row MDCT phantom study by using imaging protocols with lower tube voltage which was in consensus with an earlier study by Hurwitz et al [21, 22].…”
Section: Discussionsupporting
confidence: 92%
“…The display field of view (D-FOV) is part of the reconstruction algorithm that sets the display size, pixel size, and display characteristics and volume scan length (VSL) is the area covered by the scanner along the z -axis. The mean of five radiation dose measurements for each organ at each HR and kVp was converted into the effective organ dose by multiplying it with the appropriate tissue-weighting factor for each organ [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not use ECG modulation for LPS mode in this study. According to our previous study, LPS mode with ECG modulation reduced doses absorbed by thoracic organs by 6.4% (3.4%–9.2%) compared with those for LPS mode without ECG modulation (28) . Incidentally, for the HPS mode in our study, the effective dose estimated by the dose–length product and a conversion factor (0.014 for chest CT in adults (1) ) was 1.6 mSv, which was larger than that observed by Achenbach et al (13) because they applied a lower tube voltage of 100 kV than that used in our study.…”
Section: Discussionmentioning
confidence: 86%
“…The SAS mode results in low radiation exposure and provides high diagnostic accuracy during CHD assessments; however, this mode can only be applied in patients with stable sinus rhythms and low heart rates (4). A previous phantom study (5) also showed that the SAS mode requires a lower radiation dose than the LPS mode. The dual-source (DS)-SAS mode also yields diagnostic image quality for most coronary segments at a low radiation dose (6).…”
Section: Introductionmentioning
confidence: 99%